Loss of upper Extremity Motor Control and Function affect Women more than Men - Gad Alon (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Background: Loss of functional ability and motor control following stroke appears to affect women more severely than men in general. However, little attention has been paid specifically to the upper extremity. Objective: To quantify loss of upper extremity control, comparing men to women that survived ischemic stroke. A secondary purpose was to report gender differences in residual deficits (RD) of the paretic upper extremity following 12 weeks of rehabilitation.  Design: A retrospective data analyses from women (n=21) and men (n=24) that received task-specific (control) or task-specific + functional electrical stimulation (FES) training to the paretic upper extremity. Methods: Participants performed a modified Fugl-Meyer (mF-M), the Box & Blocks and the Jebsen-Taylor light object lift tests. Baseline and post 12-week training data of women and men were compared statistically (p=0.05). RD was calculated as= (1-(paretic/non-paretic))*100.  Results: Females had significantly greater loss of upper extremity control compared to male subjects (9.3±8.6 vs. 14.8±12.0 mF-M score; 0.7±1.9 vs. 4.5±6.6 transferred blocks; and 60±0 vs. 49.9±18.3 sec completing the Jebsen-Taylor test). Females' RD were significantly higher performing the mF-M and Box & Blocks than the males' RD. The Jebsen-Taylor test's RD did not differ statistically between the genders. Limitations: The study was not based on prospective analysis of data where gender is considered a factor in the original experimental design.  Conclusion: Loss of upper extremity control is considerably more evident in females following first-time ischemic stroke. The recovery rate associated with task-specific rehabilitation with or without FES appears similar in a sub-group with good prognosis. The deficits of motor control and hand function of females with poor prognosis remain significantly higher than the deficits of males with similar prognosis.